Improvement of German Language Skills through Participation in PASCH-Jugendkurs - Iwa Sobara (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
Since 2008, the Goethe-Institut has organized PASCH-Jugendkurs for students from partner schools around the world through the initiative of “Schools: Partners of the Future” (PASCH). One of the main objectives of PASCH-Jugendkurs is to improve students' language skills. During the three-week youth course, scholarship holders have the interesting experience of learning German in the international learning community. They learn with many friends from many different cultures and countries. This gives participants the opportunity to be friends of the same age and to exchange ideas with other participants from different countries. Most of PASCH-Jugendkurs participants from Indonesia made significant progress after participating in PASCH-Jugendkurs. 77.73% of all participants showed an improvement in their German language skills. When interacting with participants from various countries, they sometimes encounter obstacles especially in communication. Language barriers, cultural differences, differences of temperament and character and age differences are the reasons given by the participants and the inhibiting factors they face when communicating with friends from different cultural and language backgrounds. However, the positive impressions they receive in the PASCH-Jugendkurs will definitely bring them back to their home country.